Surface‐Assisted Self‐Assembly of a Hydrogel by Proton Diffusion. (30th July 2018) - Spitzer, Daniel; Marichez, Vincent; Formon, Georges J. M.; Besenius, Pol; Hermans, Thomas M.
Abstract: Controlling supramolecular growth at solid surfaces is of great importance to expand the scope of supramolecular materials. A dendritic benzene‐1, 3, 5‐tricarboxamide peptide conjugate is described in which assembly can be triggered by a pH jump. Stopped‐flow kinetics and mathematical modeling provide a quantitative understanding of the nucleation, elongation, and fragmentation behavior in solution. To assemble the molecule at a solid–liquid interface, we use proton diffusion from the bulk. The latter needs to be slower than the lag phase of nucleation to progressively grow a hydrogel outwards from the surface. Our method of surface‐assisted self‐assembly is generally applicable to other gelators, and can be used to create structured supramolecular materials.